The Effect of Learning Model and Math Ability on Student Learning Outcomes on the Subject of Chemical Equilibrium - Simorangkir, Ledy Paulina; Silitonga, Pasar Maulim (Universitas Lampung, 2024)
The Influence of Learning Models and Mathematical Abilities on Student Learning Outcomes on the Subject of Chemical Equilibrium. This research aims to determine the influence of learning models, mathematical abilities and the interaction between learning models and mathematical abilities on student learning outcomes on the subject of chemical equilibrium. The research population was all 10 class XI students of SMA Negeri 1 Percut Sei Tuan. Samples were taken in two stages, namely: first, 2 class samples were taken randomly. In the second stage, each class was divided into 2 groups, namely a high mathematics ability group consisting of 10 people and a low mathematics ability group of 10 people so that the total sample of students used was 40 people. This research used a 2 x 2 complete random factorial design. There were two factors tested, namely factor A: Learning Model which consisted of 2 levels, namely A1 = Problem Based Learning and A2 = Discovery Learning, factor B: Students' mathematical abilities which consisted of 2 levels namely B1 = high mathematical ability and B2 = low mathematical ability. Based on hypothesis testing at a significance level of α = 0.05, it was found that Fhit (A) = 26.61 and Fhit (B) = 10.53 while Ftable = 4.11. Thus, Fhit (A) > Ftable, which means that there is an influence of the learning model on student learning outcomes on the subject of chemical equilibrium. Likewise, Fhit (B) > Ftable means that there is an influence of mathematical ability on student learning outcomes. Furthermore, we obtained Fhit (AB) > Ftable or 7.15 > 4.11, meaning that there is an interaction between the learning model and mathematical abilities on student learning outcomes on the subject of chemical equilibrium.Keywords: Problem-Based Learning, Discovery Learning, Mathematics Ability, Learning Outcomes, Chemical Equilibrium DOI: 10.23960/jppk.v13i2.30259